Metagenomic evidence of a novel family of anammox bacteria in a subsea environment. (18th April 2022) - Suarez, Carolina; Dalcin Martins, Paula; Jetten, Mike S.M.; Karačić, Sabina; Wilén, Britt Marie; Modin, Oskar; Hagelia, Per; Hermansson, Malte; Persson, Frank
Summary: Bacteria in the order ' Candidatus Brocadiales' within the phylum Planctomycetes ( Planctomycetota ) have the remarkable ability to perform anaerobic ammonium oxidation (anammox). Two families of anammox bacteria with different biogeographical distributions have been reported, marine Ca . Scalinduaceae and freshwater Ca . Brocadiaceae. Here we report evidence of three new species within a novel genus and family of anammox bacteria, which were discovered in biofilms of a subsea road tunnel under a fjord in Norway. In this particular ecosystem, the nitrogen cycle is likely fuelled by ammonia from organic matter degradation in the fjord sediments and the rock mass above the tunnel, resulting in the growth of biofilms where anammox bacteria can thrive under oxygen limitation. We resolved several metagenome‐assembled genomes (MAGs) of anammox bacteria, including three Ca . Brocadiales MAGs that could not be classified at the family level. MAGs of this novel family had all the diagnostic genes for a full anaerobic ammonium oxidation pathway in which nitrite was probably reduced by a NirK‐like reductase. A survey of published molecular data indicated that this new family of anammox bacteria occurs in many marine sediments, where its members presumably would contribute to nitrogen loss.